Viewpoint – Why Has the South African National Water Act Been so Difficult to Implement? - Barbara Schreiner (Water Alternatives, 2013)
The South African National Water Act (Act 36 of 1998) was hailed by the international water community as one of the most progressive pieces of water legislation in the world, and a major step forward in the translation of the concept of integrated water resources management (IWRM) into legislation. It has been widely quoted and referred to, and a number of countries ranging from China to Zambia have used it as an example in the revision of their own water legislation. And yet, 15 years down the line, implementation of the act has been only partially successful. In a number of critical aspects, implementation has, in fact, been weak. This paper sets out some personal reflections on the challenges facing the implementation of this remarkable piece of legislation and on the failure to achieve the initial high ambitions within the South African water sector. Through this process, it may be that there are lessons for other countries and for South Africa itself as it continues to face the challenge of implementation of the National Water Act (NWA).